2012
DOI: 10.3892/or.2012.1899
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of miR-1-1 and miR-133a-2 cluster expression by DNA hypermethylation in colorectal cancer

Abstract: MicroRNAs are small non-coding RNA molecules that play important roles in the multistep process of colorectal carcinoma (CRC) development. The present study evaluated the relationship between miR-1-1 and miR-133a-2 expression and DNA methylation, and its putative biological role in CRC. The results indicated that DNA methylation regulated the expression of the miR-1-1 and miR-133a-2 cluster in CRC cell lines. Expression of miR-1 and miR-133a was furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
39
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 42 publications
(52 reference statements)
2
39
1
Order By: Relevance
“…Epigenetic silencing of miRNAs with tumor suppressor features by CpG island hypermethylation is a common hallmark of human tumors (11). Most recently, it was documented that hypermethylation of the CpG islands upstream of miR-1-133a might be involved in the downregulation of miR-133a in CRCs (12). In the present study, we showed that miR-133a was significantly downregulated in primary CRC tissues using microdissection technique.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Epigenetic silencing of miRNAs with tumor suppressor features by CpG island hypermethylation is a common hallmark of human tumors (11). Most recently, it was documented that hypermethylation of the CpG islands upstream of miR-1-133a might be involved in the downregulation of miR-133a in CRCs (12). In the present study, we showed that miR-133a was significantly downregulated in primary CRC tissues using microdissection technique.…”
Section: Discussionsupporting
confidence: 59%
“…Chen and colleagues mentioned that patients with CRC with liver metastasis were associated with lower expression of miR-133a (12). Unfortunately, we did not observe such Figure 6.…”
Section: Discussioncontrasting
confidence: 56%
“…In our previous study, miR1/133a suppressed the tumor growth and metastasis in colorectal cancer by directly targeting LASP1 3 0 UTR (10). DNA methylation inhibits the expression of miR1/133a, which could be indirectly upregulated with LASP1 expression (47). Moreover, the stimulation of TGFb significantly induces the expression of LASP1 in a time-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic expression of miR-1-1 in HepG2 cells caused a reduction in cell proliferation, growth and clonogenic survival by inducing apoptosis and inhibiting cell cycle progression, and mitigated the cancer-cell characteristics of these cells. Therapeutic intervention with hypomethylating agents could inhibit HCC cell growth by increasing miR-1-1 expression to inhibit expression of its two downstream oncogenes, MET (MNNG HOS transforming gene) and FoxP1 (Forkhead box protein P1) [80]. These data imply that compounds interfering with epigenetic modifications, such as DNMT and histone deacetylase inhibitors, may serve as potential novel antitumor drugs for HCC patients [81,82].…”
Section: Mirnas Add Complexity To Epigenetic Modificationmentioning
confidence: 99%